2021
DOI: 10.1002/clc.23559
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anemia on clinical outcomes of patients with atrial fibrillation: The COOL‐AF registry

Abstract: Background To determine whether anemia is an independent risk factor for ischemic stroke and major bleeding in patients with non‐valvular atrial fibrillation (NVAF). Hypothesis Anemia in patients with NVAF increase risk of clinical complications related to atrial fibrillation. Methods We conducted a prospective multicenter registry of patients with NVAF in Thailand. Demographic data, medical history, comorbid conditions, laboratory data, and medications were collected and recorded, and patients were followed‐u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…We have shown that individuals with XLI (or female carriers of associated genetic deletions) are strongly in favour of cardiac screening shortly after diagnosis to mitigate long-term health consequences associated with AHRs for them and their offspring. As such, the utility and viability of screening within these populations, and particularly in individuals with comorbid GI disorders, asthma or anaemia where clinical prognosis appears worse,47 48 should be investigated. Our results further indicate that routine targeted cardiac screening of both male and female Xp22.31 deletion carriers may be warranted, irrespective of whether they present with XLI-associated phenotypes or not.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that individuals with XLI (or female carriers of associated genetic deletions) are strongly in favour of cardiac screening shortly after diagnosis to mitigate long-term health consequences associated with AHRs for them and their offspring. As such, the utility and viability of screening within these populations, and particularly in individuals with comorbid GI disorders, asthma or anaemia where clinical prognosis appears worse,47 48 should be investigated. Our results further indicate that routine targeted cardiac screening of both male and female Xp22.31 deletion carriers may be warranted, irrespective of whether they present with XLI-associated phenotypes or not.…”
Section: Discussionmentioning
confidence: 99%
“…55 A growing number of studies have shown that patients with AF complicated by anemia are more likely to be at risk for bleeding, cardiac events, and death from all causes. 56 Recent cohort studies also suggest that low hemoglobin levels and anemia may be associated with the development of new-onset AF. 57 However, the reasons for these associations are unclear and little research has been done.…”
Section: Iron Deficiencymentioning
confidence: 99%
“…As easily as AF is found in the elderly people, the incidence of anemia is higher in the elderly people 55 . A growing number of studies have shown that patients with AF complicated by anemia are more likely to be at risk for bleeding, cardiac events, and death from all causes 56 . Recent cohort studies also suggest that low hemoglobin levels and anemia may be associated with the development of new‐onset AF 57 .…”
Section: Iron Deficiencymentioning
confidence: 99%
“…Furthermore, anemia was associated with a 15% increased hazard of stroke or systemic thromboembolism, and 78% increased hazard of major bleeding. More recently, several cohort studies have also reported associations of anemia with greater risks of heart failure hospitalization [ 67 – 69 ]. Furthermore, at least one study has also suggested that anemia may associated with clinical recurrence of AF [ 14 ].…”
Section: Existing Data On Anemia and Atrial Fibrillationmentioning
confidence: 99%